2012
DOI: 10.1007/s12199-012-0275-9
|View full text |Cite
|
Sign up to set email alerts
|

Changes in mental health and quality of life with dental implants as evaluated by General Health Questionnaire (GHQ) and Health Utilities Index (HUI)

Abstract: Objectives The purpose of this study was to assess and compare the improvement in oral and systemic conditions and health-related quality of life in patients with missing teeth receiving dental implants and conventional treatment. Methods A total of 97 patients with missing teeth, of whom 59 received dental implants and 38 received conventional treatment, were included in this study. The patients were divided into two age groups for a more detailed analysis: a 30-to 59-year age group (young) and a [60-year age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…For GHQ-12 scoring, each item response category was scored using a 4-point scale (0-0-1-1), with total scores ranging from 0-12 points. According to the evaluation standards for level of mental health in the Japanese version of the GHQ-12 (Takemae et al 2012), a score of > 3 was designated as the high (= good) GHQ group, and a score of < 3 was designated as the low (= poor) GHQ group.…”
Section: Questionnaire Items Soc-13 and Ghq-12mentioning
confidence: 99%
“…For GHQ-12 scoring, each item response category was scored using a 4-point scale (0-0-1-1), with total scores ranging from 0-12 points. According to the evaluation standards for level of mental health in the Japanese version of the GHQ-12 (Takemae et al 2012), a score of > 3 was designated as the high (= good) GHQ group, and a score of < 3 was designated as the low (= poor) GHQ group.…”
Section: Questionnaire Items Soc-13 and Ghq-12mentioning
confidence: 99%
“…Shimada reported that function, presence of pain and patient acceptance are factors related to general and psychological health (Shimada, 1995). Overall, patient acceptance is an important factor in dental treatments affecting quality of life and higher life standards (Takemae et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Before implant surgery, all participants signed a consent form and scaling procedure was carried out for each participant in need of it. Based on similar studies, 102 patients were selected using convenient sampling method (Heo, Heo, Chang, & Park, 2008; Pavel et al, 2012; Takemae et al, 2012; Yoshida et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Dental implants are globally well accepted as the best choice for replacement of missing teeth, 1 because they do not involve any other teeth preparation, have better psychological acceptance by patients, 2 better load distribution 3 and a better preservation of periodontal tissue (alveolar bone and gingiva.) 4 …”
Section: Introductionmentioning
confidence: 99%